National income and its distribution in preindustrial Poland in a global perspective - Nikolaj Malinowski; Jan Luiten van Zanden (European Historical Economics Society (EHES), 2015)
This paper presents estimates of the level of per capita GDP and of the distribution of income of preindustrial Poland. This is based on a reconstruction of a social table of the Voivodeship of Cracow for 1578. Our evidence indicates that income in Poland was distributed more equally than in contemporary Holland. However, the extraction rate in the Voivodeship was much higher than in the North Sea area. Furthermore, income inequality in the countryside of the Voivodeship was higher than inequality in Cracow. This can be linked to the demesne economy based on serfdom that was prevalent in the agricultural sector. Moreover, on the basis of trends in real wages and urbanisation levels, we project Polish GDP forwards and backwards in time. Our results indicate that by as early as the 15th century, Polish per capita GDP was below that of other Western European countries. This persisted despite a moderate growth of the Polish economy in the 16th century. Subsequently, due to a strong contraction, Poland in the 17th century became even poorer than Asian economies for which similar estimates are available. In the 18th century Poland recovered slightly but continued to lag behind the rest of Western Europe.
Keywords: N13; N33; 330; Economic growth; Income inequality; 'Great Divergence'; Poland; Extraction ratio; Serfdom